Caponi, Sandra. Uma sala tranquila: neurolépticos para uma biopolítica da indiferença. São Paulo: Liber Ars, 2019, 216 p. - Márquez Valderrama, Jorge; Ortiz Lopera, Wilson Daniel (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Review